Detection of Disease-Causing SNVs/Indels and CNVs in Single Test Based on Whole Exome Sequencing: A Retrospective Case Study in Epileptic Encephalopathies - Sun, Dan; Liu, Yan; Cai, Wei; Ma, Jiehui; Ni, Kun; Chen, Ming; Wang, Cheng; Liu, Yongchu; Zhu, Yuanyuan; Liu, Zhisheng; Zhu, Feng (Frontiers in Pediatrics, 2021)
Background: Epileptic encephalopathies(EEs) is a pediatric entity with highly phenotypic and genetic heterogeneity. Both single nucelotide variants(SNVs)/indels and copy number variations (CNVs) could be causative. Whole exome sequencing (WES) is widely applied to detect SNVs/Indels, but the bioinformatics approach for detecting CNVs maybe limited or powerless. In current study, we evaluated the possibility of profiling both disease-causing SNPs/Indels and CNVs in a single test based on WES in EEs. Methods: The infants diagnosed with EEs were enrolled from a single pediatric epilepsy center between January 2018 and February 2020. Demographic and clinical data were collected. In WES data, the pathogenic SNVs were identified through an in-house pipeline, and pathogenic CNVs were identified by CNVkit. The diagnostic rate were evaluated and the molecular findings were characterized. Results: A total 73 infants were included; 36 (49.32%) of them were males. The median age was 7 months. 32(43.84%) infants had diagnosis of an epilepsy syndrome. Most common type of syndrome was West syndrome (22/73, 30.1%), followed by Dravet syndrome (20/77, 27.4%). 54(73.97%) had intellectual development delay. The genetic cause of EEs, pathogenic or likely pathogenic variants, were successfully discovered for 49.3%(36/73) infants, and 31(42.5%) infants carried SNVs/Indels and 5(6.8%) carried CNVs. The majority of the variants were inherited in de novo pattern(21, 63.6%). In addition to the fact that variants in the ion channel encoding genes account for the main etiology, we found that two newly confirmed disease-causing genes, CACNA1E and WDR26. Five discovered CNVs were deletions of 2q24.3, 1p36, 15q11-q13, 16p11.2 and 17p13.3, and all had been confirmed by array comparative genomic hybridization. Conclusion: The application of detecting both SNPs/Indels and CNVs in single test based on WES yielded a high diagnosis rate in EEs. WES may be severed as a first-tier test with cost-effective benefit in EEs.